(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article analyzes the prospective directions for the creation of sustainable jobs. Based on the reports of the World Economic Forum and the International Labour Organization, it is substantiated that by 2030, under the influence of technological progress and the green economy, new professions will emerge, while a number of traditional occupations are expected to disappear.